Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am looking for the "best" way to determine whether a function is one-to-one, either algebraically or with calculus. I know a common, yet arguably unreliable method for determining this answer would be to graph the function. However, this can prove to be a risky method for finding such an answer at it heavily depends on the precision of your graphing calculator, your zoom, etc...

What is the best method for finding that a function is one-to-one? In your description, could you please elaborate by showing that it can prove the following:

This is one-to-one: $\frac{x-3}{x+2}$

This is not one-to-one: $\frac{x-3}{x^3}$

share|cite|improve this question
Composition of 1-1 functions is also 1-1. – Nick Alger Jan 24 '12 at 15:19
See this previous question – Arturo Magidin Jan 24 '12 at 15:38
up vote 38 down vote accepted

To show that $f$ is 1-1, you could show that $$f(x)=f(y)\Longrightarrow x=y.$$ So, for example, for $f(x)={x-3\over x+2}$:

Suppose ${x-3\over x+2}= {y-3\over y+2}$. Then: $$ \eqalign{ &{x-3\over x+2}= {y-3\over y+2} \cr \Longrightarrow& (y+2)(x-3)= (y-3)(x+2)\cr \iff& yx+2x-3y-6= yx-3x+2y-6\cr \iff&2x-3y =-3x+2y\cr \iff&2x+3x =2y+3y\cr \iff&5x =5y\cr \iff&x=y. } $$ So $f(x)={x-3\over x+2}$ is 1-1.

I'll leave showing that $f(x)={{x-3}\over 3}$ is 1-1 for you.

Alternatively, to show that $f$ is 1-1, you could show that $$x\ne y\Longrightarrow f(x)\ne f(y).$$

Or, to show that a differentiable $f$ is 1-1, you could show that its derivative $f'$ is either always positive or always negative.

You would discover that a function $g$ is not 1-1, if, when using the first method above, you find that the equation is satisfied for some $x\ne y$. For example, take $g(x)=1-x^2$. Then

$$ \eqalign{ &g(x)=g(y)\cr \iff&{1-x^2}= {1-y^2} \cr \iff&-x^2= -y^2\cr \iff&x^2=y^2\cr} $$ The above equation has $x=1$, $y=-1$ as a solution. So, there is $x\ne y$ with $g(x)=g(y)$; thus $g(x)=1-x^2$ is not 1-1.

Of course, to show $g$ is not 1-1, you need only find two distinct values of the input value $x$ that give $g$ the same output value.

Although you rightfully point out that the graphical method is unreliable; it is still instructive to consider the methods used and why they work:

Graphically, you can use either of the following:

  1. Use the "Horizontal Line Test":

    $f$ is 1-1 if and only if every horizontal line intersects the graph of $f$ in at most one point. Note that this is just the graphical interpretation of "if $x\ne y$ then $f(x)\ne f(y)$"; since the intersection points of a horizontal line with the graph of $f$ give $x$ values for which $f(x)$ has the same value (namely the $y$-intercept of the line).

  2. Use the fact that a continuous $f$ is 1-1 if and only if $f$ is either strictly increasing or strictly decreasing. This, of course, is equivalent to the derivative being always positive or always negative in the case where $f$ is differentiable. (Note this method applies to only the green function below.)

    enter image description here

share|cite|improve this answer
Thank you for your time! Points up and answer accepted! – Oliver Spryn Jan 24 '12 at 17:30
What if the equation in question is the square root of x? Obviously it is 1:1 but I always end up with the absolute value of x being equal to the absolute value of y. What have I done wrong? – louie mcconnell Jul 17 '14 at 9:37
@louiemcconnell The domain of the square root function is the set of non-negative reals. Keep this in mind when solving $|x|=|y|$ (you actually solve $x=|y|$, $x\ge 0$). – David Mitra Jul 17 '14 at 9:43

A one-to-one function is an injective function. A function $f:A\rightarrow B$ is an injection if $x=y$ whenever $f(x)=f(y)$.

Both functions $f(x)=\dfrac{x-3}{x+2}$ and $f(x)=\dfrac{x-3}{3}$ are injective.

Let's prove it for the first one

$$ \begin{eqnarray*} f(x) &=&f(y)\Leftrightarrow \frac{x-3}{x+2}=\frac{y-3}{y+2} \\ &\Rightarrow &\left( y+2\right) \left( x-3\right) =\left( y-3\right) \left( x+2\right) \qquad(\text{for }x\neq-2,y\neq -2)\\ &\Rightarrow &xy-3y+2x-6=xy+2y-3x-6 \\ &\Rightarrow &-3y+2x=2y-3x\Leftrightarrow 2x+3x=2y+3y \\ &\Rightarrow &5x=5y\Rightarrow x=y. \end{eqnarray*}$$

So we concluded that $f(x) =f(y)\Rightarrow x=y$, as stated in the definition.

As for the second, we have $$ \begin{eqnarray*} f(x) =f(y)\Leftrightarrow \frac{x-3}{3}=\frac{y-3}{3} \Rightarrow &x-3=y-3\Rightarrow x=y. \end{eqnarray*} $$

An example of a non injective function is $f(x)=x^{2}$ because $$ \begin{eqnarray*} f(x) =f(y)\Leftrightarrow x^{2}=y^{2} \Rightarrow x=y\quad \text{or}\quad x=-y. \end{eqnarray*} $$

share|cite|improve this answer
Excellent answer. Points up! – Oliver Spryn Jan 24 '12 at 17:30
@spryno724: Thanks! – Américo Tavares Jan 24 '12 at 20:49
Since your answer was so thorough, I'll +1 your comment! – Oliver Spryn Jan 24 '12 at 21:45

For your modified second function $f(x) = \frac{x-3}{x^3}$, you could note that $$f(x) - f(y) = \frac{(x-y)((3-y)x^2 +(3y-y^2) x + 3 y^2)}{x^3 y^3}$$ As a quadratic polynomial in $x$, the factor $ (3-y)x^2 +(3y-y^2) x + 3 y^2$ has discriminant $y^2 (9+y)(y-3)$. So when either $y > 3$ or $y < -9$ this produces two distinct real $x$ such that $f(x) = f(y)$.

share|cite|improve this answer

protected by Community Jun 30 '14 at 20:16

Thank you for your interest in this question. Because it has attracted low-quality or spam answers that had to be removed, posting an answer now requires 10 reputation on this site (the association bonus does not count).

Would you like to answer one of these unanswered questions instead?

Not the answer you're looking for? Browse other questions tagged or ask your own question.